2023
DOI: 10.21037/tp-22-401
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of gastric antisecretory drugs in pediatric patients with gastroesophageal reflux disease: a narrative review

Abstract: Gastroesophageal reflux (GER) is widespread in the pediatric population, especially in infants under 3 months of life where daily episodes of regurgitation are common (1). Usually, GER resolves spontaneously in 95% of infants within 12-14 months of age (2) and causes few or no symptoms (functional GER), but some children may develop symptomatic gastroesophageal reflux disease (GERD) (3).The disease manifestations are different in children compared to adults and vary considerably by age group,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…While the results showed that PPIs are the treatment of choice in pediatric GERD for patients aged 1 year and up, it did not find them useful in treating children under the age of 1 year that presented with unspecific symptoms such as crying, irritability, or apnea, particularly when they had no proven esophagitis or complications due to gastroesophageal reflux. Also, it concluded that there is no strong evidence in treating with PPIs asthma symptoms in children with GERD as they might actually be caused by the quantity of refluxed fluid and not by its quality, i.e., by its pH [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the results showed that PPIs are the treatment of choice in pediatric GERD for patients aged 1 year and up, it did not find them useful in treating children under the age of 1 year that presented with unspecific symptoms such as crying, irritability, or apnea, particularly when they had no proven esophagitis or complications due to gastroesophageal reflux. Also, it concluded that there is no strong evidence in treating with PPIs asthma symptoms in children with GERD as they might actually be caused by the quantity of refluxed fluid and not by its quality, i.e., by its pH [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management for GER was classified based on the following treatment plan [1,3,23,26–28] : grade 0 (Fig. 1), non-pharmacological treatment, such as body positioning, and feeding modifications, including decreased feed volume and slower feeding; grade 1 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Central nervous system disorders that required medical support included mental retardation, epilepsy, intraventricular hemorrhage, cerebral palsy, and hypoxic-ischemic encephalopathy. [20][21][22][23][24][25] The management for GER was classified based on the following treatment plan [1,3,23,[26][27][28] : grade 0 (Fig. 1), non-pharmacological treatment, such as body positioning, and feeding modifications, including decreased feed volume and slower feeding; grade 1 (Fig.…”
Section: Patients' Characteristics and Classificationmentioning
confidence: 99%
“…In addition, continuous stimulation by aggressive factors induces gastric mucosal inflammation, which can develop into gastric ulcers and cancer; therefore, it is crucial to control this mechanism 14 , 15 . Drugs such as ranitidine, omeprazole, and cimetidine are used to protect and treat the gastric mucosa against these aggressive factors; however, because of the side effects caused by these drugs, it is necessary to develop other safe and effective therapeutic drugs 13 , 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%